Massive Dirac-Pauli physics in lead-halide perovskites - Abhishek Shiva Kumar; Mikhail Maslov; Mikhail Lemeshko; Artem G. Volosniev; Zhanybek Alpichshev (npj Quantum Materials)
Abstract In standard quantum electrodynamics (QED), the so-called non-minimal (Pauli) coupling is suppressed for elementary particles and has no physical implications. Here, we show that the Pauli term naturally appears in a known family of Dirac materials—the lead-halide perovskites, suggesting a novel playground for the study of analog QED effects. We outline measurable manifestations of the Pauli term in the phenomena pertaining to (i) relativistic corrections to bound states (ii) the Klein paradox, and (iii) spin effects in scattering. In particular, we demonstrate that (a) the binding energy of an electron in the vicinity of a positively charged defect is noticeably decreased due to the polarizability of lead ions and the appearance of a Darwin-like term, (b) strong spin-orbit coupling due to the Pauli term affects the exciton states, and (c) scattering of an electron off an energy barrier with broken mirror symmetry produces spin polarization in the outgoing current. Our study adds to the understanding of quantum phenomena in lead-halide perovskites and paves the way for tabletop simulations of analog Dirac-Pauli equations.